Socially addept : teaching social skills to children with ADHD, LD, and Asperger's - Giler, Janet Z. (San Francisco : Jossey-Bass, 2010)
'Decodes the often confusing rules of social behavior for all children Socially ADDept helps educators and parents teach the hidden rules of social behavior to children with limited social skills, notably those with special needs like ADHD, learning disabilities, Asperger's and high-functioning autism, Tourette Syndrome, and nonverbal learning disabilities. The author provides all the information parents and professionals need to know to help kids learn social skills in simple, concise explanations. The book is divided into eight sections that educators can use as teaching units or parents can work through one week (or month) at a time. Includes a way for children to see themselves and how their behavior looks to others. Deciphers the complex rules of nonverbal language into friendly, bite-sized morsels that kids can understand. Offers a field-tested collection of suggestions and strategies for parents and professionals who want to enhance a child's social competence. Socially ADDept is presented in a hands-on workbook format, complete with reproducible student worksheets that are also available for free download from the publisher web site.'--
Includes bibliographical references and index
Keywords: Learning disabled children; Behavior disorders in children; Social skills in children